Chapter A first assessment of microplastics in the sea waters off the Puglia region - Dalle Mura, Ilaria (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
To meet the objectives of the MSFD, 2008/56/EC, the Puglia Regional Agencies for the Prevention and Protection of the Environment (ARPA Puglia) performed a quantitative and qualitative analysis of the MPs on the basis of the data collected during 2015-2017 monitoring program. A total of 90 samples in 5 campaigns were collected using a manta net. The MPs average density of 0,469 n/m³ was calculated for the entire dataset. No significant statistical differences were detected among sampling sites, campaigns and distance from the coast.